Diagenesis and reservoir quality of the second member of the Upper Triassic Xujiahe Formation tight gas sandstones in the Western Sichuan Depression, southwest China. (14th February 2021) - Pan, Bo; Chen, Hongde; Lin, Liangbiao; Yu, Yu; Wu, Dong; Dong, Yixin
Abstract : The tight sandstones reservoir of the second member of the Xujiahe Formation (Xu2 member) is gradually becoming the main reservoir for natural gas exploration and exploitation in the Western Sichuan Basin. The tight sandstone is normally deeply buried, where it is controlled by complex diagenetic processes. To gain insights into reservoir exploration of the Xu2 member, the diagenetic history and the impacts of diagenesis on reservoir quality were established using several experimental methods. The sandstones were found to be mainly litharenite, sublitharenite, and feldspathic litharenite. The reservoir quality was characterized by low porosity (3.4% on average), low permeability (0.17 mD on average), low pore throat radius, and high displacement pressure. The tight sandstones experienced a series of significant diagenetic processes, including mechanical compaction, early dissolution, and precipitation of carbonate and siliceous cements during eodiagenesis. They also underwent chemical compaction, late dissolution, and transformation of clay minerals during mesodiagenesis. The silica cementation mainly resulted from chemical compaction, feldspar dissolution, and the transformation of clay minerals. A higher degree of compaction has a vital role in destroying most of the primary pores. Cementation had a significant impact on reducing the porosity and permeability, although chlorite preserved primary pores by slowing the compaction. This study aimed to provide a comprehensive insight into diagenesis and its impact on the reservoir quality of deeply buried sandstone, and provide insights into reservoir exploration and development in deeply buried tight sandstones. Abstract : This study reconstructs the diagenetic sequences and porosity evolution by detailed diagenetic analysis. Moreover, reveal the impact of the different diagenesis on the reservoir quality.